The Relationship Between Duration of Breastfeeding and Maternal Factors - Farhad Jafari; Houriyeh Farahrooz; Zeinab Abyar; Behzad Tadayyon; Fateme Azami (Fasa University of Medical Sciences, 2015)
Background & Objective: Breast milk is the best food for infants and provides all nutritional needs for child health. Some studies have been done on the factors affecting breastfeeding, and partly, the role of factors such as maternal diseases and wrong recommendations are known.   Materials & Methods: This is a cross sectional study with descriptive and analytical aspects.  The sample includes 355 people from Tehran. Data were collected through questionnaires and were analyzed with SPSS software and statistical test. Significant level was considered at the 0.05.   Results: The average of age, weight, and height of the subjects were 42.09 years, 67.2 kg and 160.3 cm respectively. The mean  body mass index (BMI) was 26.15. More than half of mothers (59.5%) were overweight or obese. In addition, 55.5% had higher education. 45.4%  of mothers had 2 children. The average age at first birth, and last was, 24.22 and 30.86 years, respectively. 58.7% of mothers were taking Oral Contraceptives Pills (OCPs). 11.9% of mothers had never breastfed their children. The average duration of breast-feeding was 11.75 months. This study suggests that there is no statistically significant relationship between the duration of breast feeding and age, height, educational level, place of work, taking OCP, exercise and emotional status of the mother (P>0.05). However, it is associated with gaining weight and increase of BMI and age at first birth and increases with them.   Conclusion: Mothers breastfed their children about a year and duration of breastfeeding were associated with body mass index and age at first birth.